Autocrine Exosomal Fibulin-1 as a Target of MiR-1269b Induces Epithelial–Mesenchymal Transition in Proximal Tubule in Diabetic Nephropathy - Tsai, Yi-Chun; Hung, Wei-Wen; Chang, Wei-An; Wu, Ping-Hsun; Wu, Ling-Yu; Lee, Su-Chu; Kuo, Mei-Chuan; Hsu, Ya-Ling (Frontiers in Cell and Developmental Biology, 2021)
Background: Diabetic nephropathy (DN) is an increasing threat to human health and regarded to be the leading cause of end-stage renal disease worldwide. Exosomes deliver biomolecule massages and may play a key role in cell communication and the progression of DN. Methods: The cross-disciplinary study, including in vivo, in vitro, and human studies was conducted to explore the cross-talk within proximal tubular epithelial cells (PTECs) in DN. Exosomal protein from PTECs treated with high glucose (HG) was purified and examined using LC-MS/MS. Next-generation sequencing (NGS) was utilized to analyze RNAs extracted from PTECs from a type 2 diabetic patient and a normal individual. HK-2 cells were used to assess exosomal protein and its modulation and biofunction in DN. Normal individuals and type 2 diabetic patients were enrolled and non-diabetic db/m mice and diabetic db/db mice were used to validate the molecular mechanism of exosomes in DN. Results: HG stimulated PTECs to increase Fibulin-1 (FBLN1) expression, and PTECs secreted FBLN1 through exosome delivery, then thereby inducing epithelial mesenchymal transition (EMT) in PTECs. Transcriptome analysis found that FBLN1 expression was modulated by miR-1269b, which was downregulated by HG in HK-2 cells. While transfection of miR-1269b reversed FBLN1-mediated EMT in PTECs, miR-1269b inhibitor modulated the phenotype of PTECs toward mesenchymal type under NG condition. Most importantly, urinary FBLN1 and exosomal miR-1269b levels were correlated with the severity of kidney injury in type 2 diabetic patients. Conclusion: This study demonstrated the communication within PTECs through exosome transmission in an autocrine pattern. miR-1269b-FBLN1 epigenetic regulatory network could be a potential therapeutic strategy to prevent the progression of DN.